PERAN KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENNING PADA KAMPUS 1 DAN 2 UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Pramana, Andi; Anshory, Muhammad Iqbal; Syahputra, Hendra (Fakultas Ekonomi dan Bisnis, 2023)
The aim of this research is to analyze the influence of variablesThe Role of Leadership and Work Discipline on Employee Performance Through Job Satisfaction as an Intervening Variable on Campus 1 and 2 of Abdurachman Saleh University, Situbondo. By using the Partial Least Square (PLS) Structural equation model. The results of the direct influence hypothesis test using the Smart PLS 3.0 application. The research results show thatLeadership has a significant positive effect on job satisfaction, Work discipline has a significant positive effect on Job Satisfaction, Leadership has a significant positive effect on employee performance, Work discipline has a significant positive effect on employee performance, Job satisfaction has an insignificant negative effect on employee performance, Leadership has an insignificant negative effect on Employee performance through job satisfaction, and work discipline have an insignificant negative effect on employee performance through job satisfaction.